Habitat Bennu: Design Concepts for Spinning Habitats Constructed From Rubble Pile Near-Earth Asteroids - Miklavčič, Peter M.; Siu, John; Wright, Esteban; Debrecht, Alex; Askari, Hesam; Quillen, Alice C.; Frank, Adam (Frontiers in Astronomy and Space Sciences, 2022)
The authors explore the possibility that near-earth, rubble pile asteroids might be used as habitats for human settlement by increasing their rotation to produce spin gravity. Using previously published scaling by Maindl et al. and studies of asteroid populations, it is shown that there is no class of hollowed body that would survive the spin-up process on its own without additional reinforcement. Large solid-rock asteroids (diameter $D > 10$ km) would not have the tensile strength to withstand the required rotation rates and would fracture and break apart. Smaller asteroids, being 'rubble piles', have little tensile strength and would quickly disperse. The possibility of containing the asteroid mass using higher-strength materials like carbon nanofiber is instead considered. It is found that a moderate tensile strength container can maintain the integrity of a large spinning cylinder composed of dispersed asteroid regolith. The research extends the range of possible asteroid habitat candidates, since it may become feasible to construct habitats from the more numerous smaller bodies, including NEAs (Near Earth Asteroids). The required tensile strength of the container material scales with habitat radius and thickness and is $\sim200$ MPa for a starting asteroid body of radius 300m that is spun up to provide 0.3 $g_\oplus$ while increasing its radius to 3 km and maintaining a rubble and regolith shield thickness of 2m to protect against cosmic rays. Ambient solar power can be harvested to aid in spin-up and material processing.